South African London : Writing the metropolis after 1948 - Thorpe, Andrea (Book collections on Project MUSE., 2021)
This book presents a long-ranging and in-depth study of South African writing set in London during the apartheid years and beyond. Since London served as an important site of South African exile and emigration, particularly during the second half of the twentieth-century, the city shaped the history of South African letters in meaningful and material ways. Being in London allowed South African writers to engage with their own expectations of Englishness, and to rethink their South African identities. The book presents a range of diverse and fascinating responses by South African writers that provide nuanced perspectives on exile, global racisms and modernity. Writers studied include Peter Abrahams, Dan Jacobson, Noni Jabavu, Todd Matshikiza, Arthur Nortje, Lauretta Ngcobo, J.M.Coetzee, Justin Cartwright, and Ishtiyaq Shukri. South African London offers an original and multi-faceted take on both London writing and South African twentieth-century literature.